A kinematic analysis of trunk ability in wheelchair fencing: a pilot study - Fung, Y.; Chow, B.; Fong, D.; Chan, K. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The purpose of this study was to explore the trunk ability differences between category A and B participants in wheelchair fencing. The result showed that category B participants might perform similar performance as category A participants in maximum lunge velocity, maximum lunge angle and maximum fast return velocity. This result may provide information to International Wheelchair Fencing Committee (IWFC) for the need of research on Wheelchair Fencing Classification (WFC) to clarify the differences between these two categories of participants.